Evaluation of the 3M™ Petrifilm™ Rapid E. coli/Coliform Count Plate for the Enumeration of E. coli and Coliforms: Collaborative Study, First Action: 2018.13. (12th March 2020) - Bird, Patrick; Bastin, Benjamin; Klass, Nicole; Crowley, Erin; Agin, James; Goins, David; Bakken, Hannah; Lingle, Cari; Schumacher, April; ,
Abstract: Background: The 3M™ Petrifilm™ Rapid E. coli /Coliform Count Plate is a selective and differential sample-ready-culture medium designed for the rapid enumeration of Escherichia coli ( E. coli ) and coliforms in the food and beverage industries. Objective: The 3M Petrifilm Rapid E. coli /Coliform Count Plate was compared to the U.S. Food and Drug Administration Bacteriological Analytical Manual (BAM) Chapter 4 Enumeration of Escherichia coli and the Coliform Bacteria, the International Organization of Standards (ISO) 4832:2006 Microbiology of food and animal feeding stuffs — Horizontal method for the enumeration of coliforms—Colony-count technique, and ISO 16649-2:2017 Microbiology of food and animal feeding stuffs—Horizontal method for the enumeration of beta-glucuronidase-positive Escherichia coli—Part 2 Colony-count technique at 44 degrees C using bromo-4-chloro-3- indolyl beta-D-glucuronide methods for the enumeration of E. coli and coliforms in dry dog kibble. Method: The candidate method was evaluated using two diluents, Butterfield's phosphate buffered diluent and peptone salt solution, in a paired study design with each reference method in a multi-laboratory collaborative study following the current AOAC Validation Guidelines. Three target contamination levels and an uninoculated control level were evaluated. Results: The candidate and reference methods were not statistically different at each contamination level. Reproducibility values obtained during the collaborative study were similar between the candidate and reference methods. Conclusion: These results demonstrate that the candidate method is equivalent to the reference methods. Highlight: 3M Petrifilm Rapid E. coli /Coliform Count Plate was recommended for Official First Action status for enumeration of E. coli and coliforms in a broad range of foods and environmental surfaces.